Green Skills Readiness and Curriculum Alignment in Indonesian Vocational Schools (SMK): Evidence for Blue Economy and National Sustainability Competency 2045 - Harun Urrashid; Arya Ganendra (Enigma in Education, 2025)
The integration of green skills within vocational education curricula is a critical prerequisite for achieving sustainable development objectives, particularly in maritime nations such as Indonesia. This cross-sectional study, conducted from January to June 2024, examined green skills readiness and curriculum alignment with blue economy and sustainability frameworks among 312 teachers at Indonesian Vocational High Schools (Sekolah Menengah Kejuruan, SMK) across five regions, recruited through stratified random sampling. Data were collected using validated instruments — the Green Skills Readiness Scale (GSRS; Cronbach's α = 0.87) and the Curriculum Alignment Scale (CAS; α = 0.84) — and analyzed using descriptive statistics, Pearson correlation, chi-square tests, effect size measures, and multivariable logistic regression. The overall green skills readiness score was moderate (mean 64.4 ± 7.6; range 41.0–87.4), while curriculum alignment remained below the adequate threshold (mean 53.9 ± 7.4). Curriculum alignment was the only statistically significant factor independently associated with high green skills readiness (OR = 2.27; 95% CI: 1.80–2.87; p < 0.01; Nagelkerke R² = 0.23; model AUC = 0.81), indicating that teachers in well-aligned schools had 2.27 times greater odds of demonstrating high readiness. Blue Economy Alignment was the most deficient subscale (mean 49.4 ± 17.3). These findings highlight a critical structural gap in current SMK curricula and underscore the need for targeted national curriculum reform aligned with Indonesia's 2045 sustainability agenda and the blue economy imperative.